Gaining Aquaculture Blue Growth with Low Carbon Emission Shrimp Farming Technology - Muhammad Rifqi; Bambang Widigdo; Ali Mashar; Fitrina Nazar; Anggoro Prihutomo; Yusli Wardiatno (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Carbon emissions and their relation to shrimp farming activities getting more attention by researchers and environmentalists. Emissions of carbon and other greenhouse gases are concluded as drivers of climate change due to global warming. On the contrary, climate change is proven to determine the continuity and sustainability of shrimp farming activities. The dynamics of carbon and profitability are different for the three cultivation technologies (extensive, semi-intensive, and intensive), it caused by differences in the number and types of production inputs, and facilities and infrastructure, and also differences in productivity. This study aims to formulate the blue growth of aquaculture areas in the coastal area of Karawang Regency-West Java related to carbon emission within the DPSIR framework and use trade off analyses to obtain shrimp farming technologies alternative that are low in carbon emissions. Our conclusion to be able to reduce the carbon emissions, and increase the carbon sequestration and stock as effort for shrimp farming blue growth through optimize the spatial use supervision and increase the productivity of shrimp farming. The lowest carbon emission of shrimp farming technology are semi-intensive, intensive and extensive, respectively